Concentration of Nitric Acid Strongly Influences Chemical Composition of Graphite Oxide - Jankovský, Ondřej; Nováček, Michal; Luxa, Jan; Sedmidubský, David; Boháčová, Marie; Pumera, Martin; Sofer, Zdeněk (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Graphite oxide is the most widely used precursor for the synthesis of graphene through top-down methods. We demonstrate a significant influence of nitric acid concentration on the structure and composition of the graphite oxide prepared by graphite oxidation. In general, two main chlorate-based oxidation methods are currently used for graphite oxide synthesis: the Staudenmaier method using 98 wt % nitric acid, and the Hofmann method with 68 wt % nitric acid. However, a gradual change in nitric acid concentration allows a continuous change in the graphite oxide composition. The prepared samples are thoroughly characterised by microscopic techniques as well as various spectroscopic and analytical methods. Lowering the nitric acid concentration leads to an increase in oxidation degree, and in particular, to the concentration of epoxy and hydroxyl groups. This knowledge is not only useful for the large-scale synthesis of graphite oxide with tuneable size and chemical composition, but the use of nitric acid in lower concentrations can also reduce the overall cost of the synthesis significantly.
Keywords: graphite oxide; graphene oxide; graphene; nitric acid; electrochemistry